Cardiac Ablation Catheter Guidance by Means of a Single Equivalent Moving Dipole Inverse Algorithm. Issue 7 (28th February 2013) - LEE, KICHANG; LV, WENER; TER‐OVANESYAN, EVGENY; BARLEY, MAYA E.; VOYSEY, GRAHAM E.; GALEA, ANNA M.; HIRSCHMAN, GORDON B.; LEROY, KRISTEN; MARINI, ROBERT P.; BARRETT, CONOR; ARMOUNDAS, ANTONIS A.; COHEN, RICHARD J.
<x xml:space="preserve">Abstract</x> Background We developed and evaluated a novel system for guiding radiofrequency catheter ablation therapy of ventricular tachycardia. This guidance system employs an inverse solution guidance algorithm (ISGA) using a single equivalent moving dipole (SEMD) localization method. The method and system were evaluated in both a saline tank phantom model and in vivo animal (swine) experiments. Methods A catheter with two platinum electrodes spaced 3 mm apart was used as the dipole source in the phantom study. A 40‐Hz sinusoidal signal was applied to the electrode pair. In the animal study, four to eight electrodes were sutured onto the right ventricle. These electrodes were connected to a stimulus generator delivering 1‐ms duration pacing pulses. Signals were recorded from 64 electrodes, located either on the inner surface of the saline tank or on the body surface of the pig, and then processed by the ISGA to localize the physical or bioelectrical SEMD. Results In the phantom studies, the guidance algorithm was used to advance a catheter tip to the location of the source dipole. The distance from the final position of the catheter tip to the position of the target dipole was 2.22 ± 0.78 mm in real space and 1.38 ± 0.78 mm in image space (computational space). The ISGA successfully tracked the locations of electrodes sutured on the ventricular myocardium and the movement of an endocardial catheter placed in the animal's right ventricle. Conclusion In conclusion, we successfully demonstrated the feasibility of using an SEMD inverse algorithm to guide a cardiac ablation catheter.